Monitoring the activities of sports reserve training institutions on the example of the municipal formation "Yekaterinburg city" - Fitina, L. N.; Parygin, A. V.; Khristosova, Y. M. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to study the process of monitoring municipal institutions for training the sports reserve of the municipal formation "Ekaterinburg City".